1938
DOI: 10.6028/jres.021.015
|View full text |Cite
|
Sign up to set email alerts
|

Optical and dimensional changes which accompany the freezing and melting of Hevea rubber

Abstract: The opacity of "frozen" rubber results from crystallization of the rubber hydrocarbons. At temperatures between-15 0 and-35 0 C rubber is known to freeze in a few hours. The rubber of Hevea brasiliensis and its sol and gel fractions were frozen at about-25 0 C and maintained at that temperature for periods of 2 weeks to 3 months. Microtome sections were prepared and examined at controlled temperatures under a polarizing microscope. When unstrained rubber was studied in this way, each section appeared to be com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1941
1941
1972
1972

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It is interesting to no te that in their study of th e dimensional changes of unvulcanized natural rubber, using interferometric techniques, vVood, B ekkedahl, and P eter s [18] observed that plastic flow occurred in the vicinity of 40° C. Similarly, Smith and Saylor [19] noted that the birefringence in natural rubber caused by induced strains (not crystallites) disappeared in the range 40° to 55° C. With the observation that the crystallites in stark rubber are oriented and with the above explanation for the melting b ehavior, it is clear that the assigned values of Tm are not thermodynamically significant. The assignment of an equilibrium melting temperature to the unoriented semicrystalline natural rubber would thus appear to be justified [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to no te that in their study of th e dimensional changes of unvulcanized natural rubber, using interferometric techniques, vVood, B ekkedahl, and P eter s [18] observed that plastic flow occurred in the vicinity of 40° C. Similarly, Smith and Saylor [19] noted that the birefringence in natural rubber caused by induced strains (not crystallites) disappeared in the range 40° to 55° C. With the observation that the crystallites in stark rubber are oriented and with the above explanation for the melting b ehavior, it is clear that the assigned values of Tm are not thermodynamically significant. The assignment of an equilibrium melting temperature to the unoriented semicrystalline natural rubber would thus appear to be justified [8].…”
Section: Discussionmentioning
confidence: 99%
“…Early attempts in this direction were made by Smith and Saylor [19], who compressed a sample of amorphous natural rubber between aluminum plates for 6 months at -25° C. The resulting crystallites displayed definite orientation, but the melting point was only 10° to 11 ° C. A further experiment was performed wherein the rubber was compressed in a steel block at a pressure of 1,000 atmospheres and held at -25° C for 2 weeks. Upon removal of the sample and on subsequent heating to room temperature, the rubber remained crystalline, and its melting point was found to be about 33° to 34° C. About 1934 A. T .…”
Section: Stark Rubber Prepared In a Laboratorymentioning
confidence: 99%
“…In order to analyze the temperature coefficient data in terms of nucleation theory it is necessary to establish the equilibrium melting temperature characteristic of each elongation ratio. From statistical mechanical considerations, Flory2 calculated the relationship between the melting temperature and elongation ratio of a crosslinked network in simple extension and derived the equation Tm0 T , AH,, 2m am (7) where T, O is the equilibrium melting temperature for the undeformed network and AHn the heat of fusion per mole of statistical segments. In the derivation of the above equation, it was assumed that the crystals developed only in the direction of the extension.…”
Section: -X(t) 'V Ktnmentioning
confidence: 99%
“…The experimental data of 0 t h and Flory5 can be extrapolated to higher elongations so as to merge with the theoretical curve given by eq. (7). By means of eq.…”
Section: -X(t) 'V Ktnmentioning
confidence: 99%
“…Previous work on unvulcanized rubber (S) showed that it can be crystallized at temperatures between +10°and -40°C ., the crystals melting in a range from about 6°to 16°C. Crystallization and fusion are accompanied by changes in volume (8), heat capacity (4), light absorption (IS), birefringence (14,15,16), x-ray diffraction (9), and mechanical properties such as hardness (IS). X-ray diffraction and birefringence, of course, give the most direct evidence of crystalline structure, but in the present work change of volume, as measured in a mercury-filled dilatometer, was chosen as the criterion of crystallization or fusion.…”
mentioning
confidence: 99%